The Effect Of 5-Aminolevulinic Acid and Phosphorus on The Leaf Quality Characteristics of The Leaves of Two Spinach Cultivars - Ahmed K. M. Rasheed; Ahlam A. Hussein (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The experiment was carried out at Department of Horticulture and Landscape Engineering research station at the College of Agriculture, University of Diyala, during the 2023-2024 agricultural season. The study aimed to evaluate the effect of spraying 5-aminolevulinic acid at three concentrations of 0, 50 and 100 mg L-1 (M1, M2, M3) twice.  the first was after the plant had reached 5-6 true leaves, and the second was 21 days later. And phosphorus at three concentrations of 0, 1, and 2 ml L-1 (P1, P2, P3) twice, on some qualitative characteristic's vegetative traits of two local and Egyptian spinach cultivars (V1 and V2). The results showed that the M3 treatments was exceptional in all studied treatments, while the comparison treatment gave the lowest values for all treatment. As for spraying with phosphorus, the treatment P3 was superior in all traits, while the comparison treatment gave the lowest values for the studied treatment. The twice interaction treatment P3M3 showed superiority in all studied traits, while the comparison treatment gave the lowest values. In addition, the M3V2 treatment showed superiority in all the studied traits. The M1V1 Treatment showed   lowest the percentage of carbohydrates, while the M1V2 treatment gave the lowest values for the remaining characteristics. The interaction treatment P3V2 was superior with the highest values for all the experimental traits, while the P1V2 treatment gave the lowest values for all the traits. The triple interaction treatment P3M3V2 gave the highest values in the leaf content of total soluble carbohydrates, vitamin C and magnesium, and fresh weight.